2010
DOI: 10.2478/s11535-010-0025-1
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation with a bacterial consortium alleviates the effect of cadmium overdose in soybean plants

Abstract: Inoculating plants that have inefficient antioxidant systems with plant-associated bacteria allows them to overcome heavy metal intoxication. We monitored protein oxidation, the activity of plant defense system enzymes, and the phenolics content in soybean (Glycine max L.) during a prolonged exposure to cadmium (Cd). The assistance of the bacterial consortium reduced the bioavailability of Cd in a soil containing 10 times the metal's Standard Maximum Value (SMV). This reduced the accumulation of Cd in the soyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…However, an increase in the level of total phenolics was also observed by inoculation of P. aeruginosa in wheat plants exposed to Zn stress as a protective action [80]. The induced antioxidant mechanism through higher accumulation of total phenols was also found in soybean plants under Cd exposure [81]. They revealed that accumulation of phenolic compounds in leaves and roots are mainly due to oxidative polymerization of enzymes involved in phenylpropanoid pathway that further alters the permeability of cell wall [81].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an increase in the level of total phenolics was also observed by inoculation of P. aeruginosa in wheat plants exposed to Zn stress as a protective action [80]. The induced antioxidant mechanism through higher accumulation of total phenols was also found in soybean plants under Cd exposure [81]. They revealed that accumulation of phenolic compounds in leaves and roots are mainly due to oxidative polymerization of enzymes involved in phenylpropanoid pathway that further alters the permeability of cell wall [81].…”
Section: Discussionmentioning
confidence: 99%
“…The induced antioxidant mechanism through higher accumulation of total phenols was also found in soybean plants under Cd exposure [81]. They revealed that accumulation of phenolic compounds in leaves and roots are mainly due to oxidative polymerization of enzymes involved in phenylpropanoid pathway that further alters the permeability of cell wall [81]. The most possible mechanism involved behind the microbe-mediated stimulation of phenolic compounds in the present study is that microbes actively participate in shikimate pathway of phenol biosynthesis during stressed conditions [82].…”
Section: Discussionmentioning
confidence: 99%
“…According to Xiong et al [151], with permission a high adsorption capacity for heavy metal ions Cr(VI), Cd(II) and Cu(II), creating a promising perspective for the effective treatment of wastewater polluted with toxic metals. P. agglomerans was also among 7 strains which were proved by Zaets et al [163] to be effective in the protection of soybean plants against accumulation of toxic cadmium present in soil. Similarly, Pishchik et al [164] demonstrated that inoculation of P. agglomerans into soil highly contaminated with toxic cadmium and lead resulted in a decrease of their content by 2-3 times and 4-5 times, respectively, and furthermore, caused a significant increase of the oats yield which exceeded even the yield noted in soils not contaminated with heavy metals.…”
Section: Reduction Of Toxic Metals and Metalloids The Facultative Anmentioning
confidence: 93%
“…The plants were protected from heavy metal stress due to the activation of phenolic compounds and glutathione-S-transfers. The results suggest that microbial inoculation significantly enhanced the antioxidant activity of 10 SMV in Cd soil ( Zaets et al., 2010 ).…”
Section: Pgpr and Their Role In The Enhancement Of Heavy Metal Stress...mentioning
confidence: 97%